FINANCIAL PLANNING FOR RETIREMENT OF PRIVATE EMPLOYEES IN THAILAND: A CASE STUDY OF TTW PUBLIC COMPANY LIMITED - Piamsuwan, Natthaya (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2019)
The purpose of this research was to study the financial planning for retirement of private employees in Thailand, study the demographic factors including gender, age, education, marriage status, position and salary, and factors of information perception, understanding in financial planning, risk and return related to financial planning for retirement of private employees in Thailand. The samples were 302 employees of TTW Public Company Limited, aged 24-60 years old. The statistics used were frequency, percentage, mean, standard deviation and Chi-Square. The study found that most employees were male aged between 25-34 years old, bachelor’s degree and single with position as an officer/staff, salary between 15,001 – 25,000 Baht. Most employees received the information about financial retirement from advertising through various media, such as television, radio and online media. There was knowledge of financial planning in the moderate level and believed the investment in financial planning would help to ensure financial security at high level. The knowledge in financial planning and implementation methods were at a moderate level. The samples could accept risk and return at high level. Most employees agreed that the rate of return was the main reason to choose the investment model since most of them invested in long term financial, such as mutual funds. The purposes of investment was to improve the quality of life both before and after retirement. The proportion of investment was 11 25% of income.